(untitled) (Nóema, 2013)
The article is the consequence of some critical notes to the contribution of Paolo Bellan, arising from reading of essays of Francesco Emmolo and Carlo Sini and the assumption of a purely phenomenological perspective in the interpretation of the processes of acquisition of scientific knowledge.